The writer's handbook. - Houghton, Samuel G. (Samuel Gilbert) 1902-1975; Olsen, Udia G.; Burack, A. S. (Abraham Saul) 1908-; Kamerman, Sylvia E.; Abbe, Elfrieda (Writer, Inc., 1936)
"Manuscript market section", ed. by U.G. Olsen, 1941-44; by E.P. Werby, 1945-